A dynamic SEIPR model for the spread of hand, foot and mouth disease in sarawak - Sze, Jan Chan; Labadin, Jane; Podin, Yuwana (Universiti Teknikal Malaysia Melaka, 2017)
In Sarawak, a series of hand, foot and mouth disease (HFMD) outbreaks since 1997 started to catch the public attention. Feared and worried among society in the region had arisen followed by the unusual fatalities cases. Some clinical researches and mathematical models regarding HFMD were produced. Clinical researches revealed that there exist the incubation period and post-infection virus shedding period which are not captured together in any mathematical models so far. In this study, the SIR (Susceptible-Infected-Recovered) model is being improved by building a simple deterministic SEIPR (Susceptible-Incubation (Exposed)-Infected-Post infection virus shedding-Recovered) model. By adding the incubation and post-infection virus shedding as parts of the compartments into SEIPR model, the number of infected cases is predicted. The simulation result shows rapid spreading of HFMD viruses through cohort and the ability of the model to predict the outbreak behavior pattern in the first ten weeks. Comparison between the SEIPR model and SIR model verified SEIPR model. Validation of the model is done by comparing the simulation with the actual data in 2006. Basic reproduction number, R0 computed was 2.15 which suggesting the highly contagious HFMD is likely to spread fast. The threshold value analysed can allow the possible interventions based on the minimum proportion of the population which create the liability of disease spreading. We hope that this model can help the public health personnel to reduce the burden of the disease by planning an effective manner of intervention during the outbreaks.